Perancangan Sistem Repositori Tugas Akhir Berbasis Web Menggunakan Metode SDLC Waterfall (Studi Kasus: Fakultas Ilmu Komputer Unsika) - Suci Dwi Pratiwi; Ade Andri Hendriadi; Taufik Ridwan (Fakultas Teknik Universitas Persada Indonesia YAI, 2026)
The management of undergraduate thesis data at the Faculty of Computer Science, Universitas Singaperbangsa Karawang (Unsika), previously relied on Google Drive as a storage medium. However, the process of searching for thesis references was still performed manually because there was no repository system that supported structured searching and data classification. This study aims to design and develop a web-based undergraduate thesis repository system to facilitate the presentation, retrieval, classification, submission, and management of students' thesis data. The system was developed using the Software Development Life Cycle (SDLC) with the Waterfall model, which consists of the analysis, design, implementation, testing, and maintenance phases. Laravel was used as the development framework, while MySQL served as the database management system. System evaluation was conducted using Black Box Testing and User Acceptance Testing (UAT). The Black Box Testing results indicated that all system features functioned as expected. Meanwhile, the UAT results showed user acceptance rates of 90.4% from Faculty of Computer Science students and 80.7% from administrators, with the System Feasibility aspect achieving the highest score of 91.5%. These results indicate that the proposed system was well accepted by users and is suitable for managing and retrieving undergraduate thesis references at the Faculty of Computer Science, Universitas Singaperbangsa Karawang.